Work characteristics and occupational health: validation and proposal of a shortened version of the Work Design Questionnaire - García Izquierdo, Antonio León; Castaño Pérez, Ana M. (Anales de Psicología / Annals of Psychology, 2022)
Interest in the study of work characteristics to explain how an individual’s relationship with the work environment can lead to maladaptive responses has taken on renewed importance in the light of increasing concern for the development of healthy organizations and organizational diversity. This study aims to develop a shortened version of the Work Design Questionnaire (WDQ) with a view to facilitating its use and interpretation. The psychometric properties of this shorter questionnaire were tested in a multi-sectoral sample of workers in Spain, with due consideration given to the gender measurement invariance. For this purpose, we applied the questionnaire to a sample of 500 workers and analyzed the relationship between the answers provided to WDQ and specific occupational health variables (satisfaction, well-being and emotional exhaustion). Results showed adequate reliability and criterion-oriented validity for the shortened version of the WDQ, that is, the WDQ18-S, as well as evidence of factorial invariance across gender. We then discuss the results and their implications for the application of the WDQ in further research and the field of occupational health and psychosocial risks prevention.